Communicating by using PECS for Children with Rubinstein-Taybi Syndrome - Derwena Mohd Bazain; Safani Bari (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2017)
This study discusses communication aid using the Picture Exchange Communication System (PECS) to children with Rubinstein Taybi Syndrome (RTS). RTS's children suffer mental retardation, have the - the autistic, can not speak and can not manage themselves well. The aim of this study was to determine the effectiveness of using PECS and RTS students can improve their language to communicate better to all. Based on the theory of constructivism introduced by Gagne that emphasizes learning system must start from the simple to the complex. The study design is a case study of a child suffering from Rubinstein-Taybi syndrome. In conclusion, the PECT implemented is expected can help children’s RTS and improve their academic performance.Kajian ini membincangkan mengenai bantuan komunikasi menggunakan Picture Exchange Communication System (PECS) kepada kanak-kanak Sindrom Rubinstein Taybi (RTS). Kanak-kanak RTS ini mengalami kerencatan akal, memiliki ciri – ciri autisme, tidak boleh bertutur dan tidak boleh urus diri dengan baik. Tujuan kajian ini adalah untuk melihat keberkesanan menggunakan PECS dan murid RTS dapat meningkatkan penguasaan bahasa untuk berkomunikasi dengan lebih baik kepada semua. Berdasarkan teori konstruktivisme yang diperkenalkan oleh Gagne yang menekankan sistem pembelajaran harus bermula daripada yang mudah kepada yang rumit. Rekabecntuk kajian ini berbentuk kajian kes terhadap seorang kanak-kanak yang mengalami sindrom Rubinstein-Taybi. Kesimpulannya, diharapkan dengan adanya PECS yang dilaksanakan dapat membantu kanak-kanak RTS ini serta meningkatkan prestasi akademik mereka.DOI: http://dx.doi.org/10.17977/um029v4i12017p029